Connotation analysis and path discussion of China’s land-sea coordination policy: based on the interregional externality theory - Li, Yanping; Wang, Yuping; Liu, Dahai; Hou, Yuting (Frontiers in Marine Science, 2024)
As two spatial geographic units that are both independent of each other and closely linked, the land and sea have complex spatial interactions. Therefore, China implements the land-sea coordination policy (LSC) needs to be approached from a more macroscopic, systematic and comprehensive perspective. Based on the interregional externality theory, this study takes the land-sea coordination policy of China as an example, and focuses on the interaction process and manifestation between land and sea, and then explores the connotation and realization path of LSC.Firstly, we delineated the spatial unit and analyzed the land-sea interactions (LSI) using Vensim software. Secondly, the characteristics and manifestations of LSI are summarized from the perspective of interregional externalities. Finally, this study clarified the basic idea of implementing LSC and further propose feasible paths for promoting land and sea development in a coordinated way, with a view to providing auxiliary decision-making suggestions for promoting the realization of LSC under the overall framework of China's territorial spatial planning.